Analisis Framing Berita Hepatitis Akut pada Merdeka.com dan PikiranRakyat.com - Dewi Novi Yanti; Hendra Setiawan (Jurnal Ilmiah Wahana Pendidikan, 2022)
The epidemic problem seems to never end. Various reports related to Covid-19 over time have resulted in the reporting of other issues. One of the interesting news on the sidelines of the spread of Covid-19 is the emergence of an outbreak of acute hepatitis. The purpose of this research is to look at the framing Merdeka.com and PikiranRakyat.com in framing news of acute hepatitis. This research adopts a qualitative paradigm. and apply the concept of Pan and Kosicki framing. The results of the analysis of the two media chose the same issue in reporting an information. However, both of them framed the news of acute hepatitis with different styles of expression. In addition to displaying data on cases of acute hepatitis, Merdeka.com offers an appeal to the Indonesian people to be aware of the mysterious acute hepatitis virus. Both media have applied the concept of news. Merdeka.com displays more data related to reports received by WHO, focuses while PikiranRakyat.com on describing three cases of Indonesian people infected with acute hepatitis. Both media display images to support the ideas conveyed by the media. The difference lies in the emphasis of the facts presented. Merdeka.com presents data on several countries where cases of mysterious acute hepatitis have been found, while PikiranRakyat.com focuses on narrating statements related to three cases of hepatitis in Indonesia that have claimed victims.